Financial Health Evaluation of PT Pegadaian before and during the COVID-19 Pandemic (Journal of Business and Management, 2022)
Abstract. PT Pegadaian is a non-bank financial institution that has significance to the economy of the middle class and Micro, Small, and Medium Enterprises (MSMEs) through its pawn services. As part of a State-Owned Enterprises (SOEs), PT Pegadaian's performance is not only assessed by its business achievements but also through its success in helping the government empower society's economy, especially in times of crisis such as the current COVID-19 pandemic. Therefore, there should be a proper form of evaluation regarding the financial health of PT Pegadaian to ensure the company's sustainability. The government has set guidelines for assessing the financial health of SOEs through the Minister of State-Owned Enterprises Decree Number KEP-100/MBU/2002 concerning Assessment of the Health Level of State-Owned Enterprises. This paper intends to evaluate the financial health of PT Pegadaian from 2017 to 2021 based on the aforementioned guidelines as well as several complementary financial indicators to compare and analyze the financial health of PT Pegadaian before and during the COVID-19 pandemic. This paper uses descriptive quantitative methods to explain a number of findings using mathematical operations. This paper is expected to provide adequate understanding to various stakeholders regarding the financial condition of PT Pegadaian, especially about how the company is tackling the COVID-19 pandemic crisis and its ability to keep carrying out its strategic role in serving the society after the pandemic era. This paper found that even though the pandemic had no impact on the company’s health classifications, the company’s total weighted scores were severely deteriorating in the two years of the pandemic. The most contributing factor leading to the conditions was, in fact, the management's anticipatory decision to increase the allowance for impairment losses significantly, which proved to suppress the company’s net income. Thus, it is hoped that stakeholders can take the right attitude and course of action regarding the company in the future.Keywords: PT Pegadaian, COVID-19 Pandemic, Financial Health, SOE, MSME